The systemic inflammation markers as potential predictors of disease progression and survival time in amyotrophic lateral sclerosis - Hong, Ye; Shi, Jian-Quan; Feng, Shuai; Huang, Shi-Qi; Yuan, Zhen-Hua; Liu, Shen; Zhang, Xiao-Hao; Zhou, Jun-Shan; Jiang, Teng; Zhao, Hong-Dong; Zhang, Ying-Dong (Frontiers in Neuroscience, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a fatal and untreatable neurodegenerative disease with only 3–5 years' survival time after diagnosis. Inflammation has been proven to play important roles in ALS progression. However, the relationship between systemic inflammation markers and ALS has not been well established, especially in Chinese ALS patients. The present study aimed to assess the predictive value of systemic inflammation markers including neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), and systemic immune-inflammation index (SII) for Chinese amyotrophic lateral sclerosis (ALS).MethodsSeventy-two Chinese ALS patients and 73 controls were included in this study. The rate of disease progression was calculated as the change of Revised ALS Functional Rating Scale (ALSFRS-R) score per month. Patients were classified into fast progressors if the progression rate > 1.0 point/month and slow progressors if progression rate ≤ 1.0 point/month. The value of NLR, PLR, LMR, and SII were measured based on blood cell counts. The association between systemic inflammation markers and disease progression rate was confirmed by logistic regression analysis. Kaplan-Meier curve and Cox regression models were used to evaluate factors affecting the survival outcome of ALS patients.ResultsFor Chinese ALS patients, NLR, PLR and SII were higher, LMR was lower when compared with controls. All these four markers were proved to be independent correlated with fast progression of ALS. Both Kaplan-Meier curve and Cox regression analysis indicated that higher NLR and lower LMR were associated with shorter survival time in the ALS patients.DiscussionIn conclusion, the systemic inflammation markers, especially NLR and LMR might be independent markers for rapid progression and shorter survival time in Chinese ALS patients.